ADAPTACIÓN CURRICULAR Y SU IMPACTO EN LAS HABILIDADES COMUNICATIVAS EN LOS ESTUDIANTES DEL SEXTO AÑO DE LA ESCUELA "JORGE WASHINGTON", PARROQUIA FEBRES CORDERO, CANTÓN BABAHOYO, PROVINCIA LOS RÍOS. - CEDEÑO LOOR KRISTELL DANIELA (2024)
Curricular adaptations are adjustments made to the content, methodology, or assessment of a curriculum in order to address students' individual differences, facilitating student participation in education. Therefore, the research aims to determine the impact of curricular adaptations on the development of communicative skills in the sixth year of basic general education in the BSE "Jorge Washington"; for this purpose, a methodology was used in accordance with the types of descriptive research, while the methods were documentary, mixed approach and field research; supported through the application of student surveys and teacher interviews as a technique. Another of the findings identified is related to teacher planning; because it does not fit the educational needs and current context of education. Through the statistical tests used, it was determined that there is a strong correlation between the variables raised in the study. Another of the findings identified is related to teacher planning; because it does not fit the educational needs and current context of education. Through the statistical tests used, it was determined that there is a strong correlation between the variables raised in the study.